2019 IEEE International Conference on Fuzzy Systems (FUZZ-IEEE) 2019
DOI: 10.1109/fuzz-ieee.2019.8859011
|View full text |Cite
|
Sign up to set email alerts
|

A Measure of Structural Complexity of Hierarchical Fuzzy Systems Adapted from Software Engineering

Abstract: Hierarchical fuzzy systems (HFSs) have been seen as an effective approach to reduce the complexity of fuzzy logic systems (FLSs), largely as a result of reducing the number of rules. However, it is not clear completely how complexity of HFSs can be measured. In FLSs, complexity is commonly expressed using a multi-factorial approach, taking into consideration the number of rules, variables, and fuzzy terms. However, this may not be the best way to assess complexity in HFSs that have structures involving multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…They have been applied to various problems and have demonstrated their ability to generate more resilient and cost-effective solutions in the face of uncertainties. The interpretability of FLSs is often highlighted as one of their strengths, as they enable the modelling and processing of linguistic variables and rules that are easily understandable [15]. This interpretability is particularly valuable in applications such as knowledge extraction and decision support [16]- [18].…”
Section: A Fuzzy Logic Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…They have been applied to various problems and have demonstrated their ability to generate more resilient and cost-effective solutions in the face of uncertainties. The interpretability of FLSs is often highlighted as one of their strengths, as they enable the modelling and processing of linguistic variables and rules that are easily understandable [15]. This interpretability is particularly valuable in applications such as knowledge extraction and decision support [16]- [18].…”
Section: A Fuzzy Logic Systemmentioning
confidence: 99%
“…Razak et al suggested a method for evaluating the complexity of HFSs that takes into account the complexity of its structure, which requires several subsystems, layers, and a dynamic topology [15], [53]. Also, the approach seems to be better with its combined structure and rule-based complexity.…”
Section: B Complexitymentioning
confidence: 99%
“…Razak et al suggested a method for evaluating the complexity of HFSs that takes into account the complexity of its structure, which requires several subsystems, layers, and a dynamic topology [35], [36]. Also, the approach seems to be better has its combined structure complexity and rule-based complexity.…”
Section: Complexitymentioning
confidence: 99%